Biomechanical behavior of implants with prosthetic connection of the morse (Cone) type, with different angulations at the implant-abutment interface in multiple dental prostheses: a finite element study - Michel Faivro Almeida SERPA; Bruno Salles SOTTO-MAIOR; Carlos Eduardo FRANCISCHONE; Mateus Antunes RIBEIRO; Wellington LIMA (RGO: Revista Gaúcha de Odontologia, 2022)
ABSTRACT Objective: Evaluate the biomechanical behavior of the influence of different internal angles of conical prosthetic connections in fixed partial prostheses of three elements, through the tridimensional finite element method. Methods: Two different models of segment of the posterior portion of the mandible, with two implants with conical connections at angulations of 11.5 and 16 degrees. Afterwards, and occlusal load of 180N was used, and divided into 2 points of application on the premolar, and 400N divided into 5 points of application on the molar. Data were acquired as the tensile, compressive and shear stresses on cortical and medullary bone, and von Mises stresses on implants and prosthetic components of two implants in both in three-unit fixed partial prosthesis. In the quantitative analysis, both in cortical and medullary bone, the tension peaks in tensile, compression, and shear forces were higher for the CM16 group. Results: When analyzing qualitatively, the cortical and medullary bones presented a greater stress around the implant platform with a higher incidence in the implant in the molar region. In the von Misses analysis in both groups, the tensions were concentrated in the cervical region of the implants, in the first threads, in the premolar and molar regions. Regarding prosthetic pillars, the stress concentration was located in the region of contact with the implant. Conclusion: The increased angulation of conicity of the internal conical connections represents a determinant factor to increase in stress concentration in the implants, prosthetic components and adjacent structures, such as the cortical and medullary bone.